Thermal and Phase Change Material Properties of Comb-Like Polyacrylic Acid-Grafted-Fatty Alcohols - KAHRAMAN, MEMET VEZİR (TAYLOR & FRANCIS INC, 2018)
Poly(acrylic acid)-graft-fatty alcohol are synthesized from the esterification of polyacrylic acid with octadecanol and docosanol. The characterization of poly(acrylic acid)-graft-fatty alcohol was performed by attenuated total reflection-Fourier transform infrared spectroscopy. The thermal stability performances and phase change behaviors of poly(acrylic acid)-graft-fatty alcohol were examined by using thermogravimetric analysis system and differential scanning calorimetry. The results indicate that the poly(acrylic acid)-graft-fatty alcohol polymeric phase change materials possess good phase change properties and provide a suitable working temperature range. The heating process phase change enthalpy is measured between 112 and 122J g(-1), and the freezing process phase change enthalpy is found between 118 and 126J g(-1). The decomposition of poly(acrylic acid)-graft-fatty alcohol polymeric phase change materials started at 177 degrees C and reached a maximum of 380 degrees C. All of the obtained poly(acrylic acid)-graft-fatty alcohol polymeric phase change materials improved latent heat storage capacity in comparison with the pristine poly(acrylic acid) polymer. With the obtained results we conclude that, these materials promise a great potential in thermal energy storage applications. [GRAPHICS]
Keywords: Differential scanning calorimetry; esterification; functional polymers; synthesis; thermogravimetric analysis; ENERGY-STORAGE; PERFORMANCE; COMPOSITES; COPOLYMER